(untitled) (Global Journal of Medical Research, 2015)
India is the second most populous country in the world. Although there have been major improvements in public health care sector in since 1950’s. The country is passing through demographic and environmental transition which is adding to burden of diseases. And Health care facilities and services in the government hospitals is playing vital role of society and promoting health care service in India. And the most of the people in nilgiris living at rural part of areas and their referring to government hospitals for health check up and various major and minor diseases and health problems. Because of due to economically below poverty. This study has to reveals perception towards service quality in government hospital for their treatments, The problem of this study reveals in government hospitals were insufficient infrastructure facilities, technological aspect and medical equipments, If a response is promised in a certain time, does not happen and responding the client quickly, and insufficient doctors. Data have been collected through interview schedule in Nilgiris district.